Faktor-Faktor yang Memengaruhi Partisipasi Petani dalam Program Asuransi Usaha Tani Padi (Autp) di Desa Triyoso, Kecamatan Belitang, Kabupaten Oku Timur - Tyas, Wening; Pratama, Lisa; Azizah, Annisa Nur; Rohmah, Mushlihah; Aminoto, Ahmad (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2024)
Businesses in the agricultural sector, especially rice farming, are faced with the risk of uncertainty as a result of the negative impacts of climate change which are detrimental to farmers. One of the government's efforts to protect farmers is by establishing rice farming insurance (AUTP). However, based on data, farmer participation in the AUTP rice program is still low. Therefore, knowledge of the characteristics of the factors that influence farmers' decisions to take part in AUTP is needed to increase farmer participation in rice farming insurance programs. The research aims to look at the factors that influence farmer participation in the AUTP program. The method used is the Multiple Linear Regression method. Based on the results of the analysis, it was found that factors that had a significant influence on farmer participation in the AUTP program were age, length of farming, land area, and education. Meanwhile, the income factor has no significant effect.